PRELIMINARY STUDY OF FISH DIVERSITY IN PABEAN BAY, INDRAMAYU - Eda Putri Santi; Emmanuel Manangkalangi; M F Rahardjo (AQUASAINS, 2022)
Pabean Bay is an estuary waters in which salinity fluctuations occur. This fluctuation requires that the fish living in this location have the ability to adapt. This research is a preliminary study that aims to identify the diversity of fish species in these waters. The study was conducted from January to June 2015 with sampling at intervals of one month. Fishing was carried out at three stations, namely the inside which is the estuary of the river, the middle part and the outside of the estuary to get a representative sample. The fishing gear used are sero, and trammel nets. During the study, it was found that 78 species of fish were included in 39 families. The number of species in each sampling varies. Among the fish found were mainly the family Gobiidae (10 species) and the Family Leiognathidae, Lutjanidae, Sciaenidae and Tetraodontidae (four species each). Several fish species were found in the larval, juvenile and adult stages, and these conditions illustrate the importance of estuaries in the survival of the fish life cycle.